Influencing the Adoption of e-Government: A Systematic Literature Review - Qiyamullaily, Arista; Subriadi, Apol Pribadi (Sistemasi: Jurnal Sistem Informasi, 2024)
This Systematic Literature Review study discusses the factors that influence the adoption of e-government services with varsiability in the influence of these factors in various countries. The research confirms the importance of trust, performance expectancy, effort expectancy, social influence, and facilitating conditions in the acceptance and adoption of e-government services. Trust factors, especially related to information security and government transparency, were found to be key elements in driving e-government adoption. In addition, the expectation of benefits obtained, ease of use, and influence from the social environment also play an important role in people's decision to use the service. Suggested recommendations to increase e-government adoption involve improving technology infrastructure, supportive policies, technology training for government personnel, as well as an approach that considers local community conditions and factors. This study provides important insights for governments and agencies in improving e-government services and increasing the adoption of these technologies across various social and cultural environments.